2003
DOI: 10.1210/en.2003-0584
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Leptin Receptor Expression in the Rat Ovary

Abstract: Leptin is an important satiety hormone and reproductive regulator and is found, along with its receptors, throughout the ovary. To date, the changes in ovarian expression of both of these proteins throughout the estrous cycle has not been studied, and the examination of protein expression has not distinguished between different forms of the receptor. In this study leptin mRNA expression in the immature gonadotropin-primed rat ovary increased 3-fold after human chorionic gonadotropin administration, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 39 publications
8
55
0
4
Order By: Relevance
“…Similar results were found by Ryan et al (2003) who reported a reduction of 80% leptin at 9-h post-hCG administration. In our studies, the expression of hypothalamic leptin receptors was not altered by hCG administration, while the content of these receptors was high in both the pituitary and the ovarian tissue.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results were found by Ryan et al (2003) who reported a reduction of 80% leptin at 9-h post-hCG administration. In our studies, the expression of hypothalamic leptin receptors was not altered by hCG administration, while the content of these receptors was high in both the pituitary and the ovarian tissue.…”
Section: Discussionsupporting
confidence: 89%
“…However, we firmly believe that these findings will be useful in future investigations, since we have shown for the first time that the expression of leptin receptors along the HPO axis is clearly modified by gonadotropins in a differential manner. In previous studies using this biological model, it has been shown that eCG administration resulted in a gradual increase in plasmatic oestrogens, and that after hCG injection, these levels diminished to basal values a few hours before ovulation occurs (Espey et al 1989, 1991, Ryan et al 2003. These results, together with those obtained in this work, suggest that oestrogens could be exerting a negative feedback on the expression of leptin receptors in the hypothalamic tissue.…”
Section: Ctrlsupporting
confidence: 81%
See 2 more Smart Citations
“…The expression of leptin receptors was observed in human and rat granulosa (GC) and theca cells (Cioffi et al, 1997;Karlsson et al, 1997;Agarwal et al, 1999;Ryan et al, 2003), in luteinized GC and theca cells harvested from prepubertal gilts (in a single in vitro study) and in the porcine corpus luteum (CL) and ovarian stroma (OS; Ruiz-Cortes et al, 2000;Smolinska et al, 2007a). The ovary is also believed to be a site of leptin synthesis.…”
Section: Introductionmentioning
confidence: 99%